Hubungan Personal Hygiene Dan Kualitas Air Bersih Dengan Kejadian Stunting Pada Balita Di Desa Serakapi Kecamatan Woja Kabupaten Dompu Tahun 2023 - Anshari, Taufik; Desimal, Iwan; Astwan, Nur Wanda Januar (Lembaga Publikasi Ilmiah Nusantara, 2023)
In this world, more than 2 million deaths of children under the age of five are directly related to malnutrition, mainly due to stunting and wasting. Until now, stunting or shortness is a nutritional problem that still occurs in Indonesia (Arisman, 2010). Stunting is a problem of malnutrition that occurs for along time due to a lack of food consumption according to the body’s needs so that children experience stunting or have a height that is shorter than the standard height based on age (MCA, 2015). This research is a quantitative study using an analytical observational research design with a cross sectional method. This research was conducted on February – March 2023 in Serakapi village, Woja District, Dompu Regency. The population of the study was toddlers in Serakapi village with a sample of 117 toddlers. Data analysis using Chi Square method. The result of chi square test showed that there was a relationship between personal hygiene and stunting on toddlers in Serakapi village, Woja district, Dompu Regency in 2023, indicated by a P value of 0.014. the result of chi square test on the quality of clean water showed that the P value is 0.000 which means that there was arelationship between the quality of clean water and stunting on toddlers in Serakapi village, Woja district, Dompu Regency in 2023.